Ultraprecise Off-Axis Atom Localization With Hybrid Fields - Jia, Ning; Zhao, Xing-Dong; Qi, Wen-Rong; Qian, Jing (Frontiers in Physics, 2022)
Atom localization enables a high-precision imaging of the atomic position, which has provided vast applications in fundamental and applied science. In the present work, we propose a scheme for realizing two-dimensional off-axis atomic localization in a three-level Λ system. Benefiting from the use of a hybrid coupling field which consists of one Gaussian beam and one Laguerre-Gaussian beam, our scheme shows that the atoms can be localized in arbitrary position with a high spatial resolution. Taking account of realistic parameters, our numerical simulation predicts that the atoms can be precisely localized with a resolution of ～200 nm in the range of a radial distance of a few micrometers to the beam core. Our results provide a more flexible way to localize atoms in a two-dimensional system, possibly paving one-step closer to the nanometer-scale atomic lithography and ultraprecise microscopy.